Manajemen Strategik dalam Organisasi Non Profit - Khoirunnisaa' Khoirunnisaa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
Non-profit organizations do not generate profits for their owners, because the money received by the non-profit organization will be used to help fund the organization's operations according to the organization's goals and objectives and distributed or donated to communities in need. The cases that occurred with the dhu'afa wallet and the Ceng Hoo mosque, both organizations are non-profit or non-profit organizations that have problems in maximizing management functions, namely program planning. Therefore, this article aims to explain non-profit or non-profit organizations and the stages of strategic management which include planning or program planning. Strategic management consists of 3 stages, namely strategy formulation, strategy implementation and strategy evaluation. The method used is a qualitative method with a library research and content analysis approach. Data analysis consists of data reduction, data presentation and data verification. This data analysis is inductive.